A genre-based study of shell-noun use in the N-be-that construction in popular and professional science articles. (October 2017) - Liu, Qingrong; Deng, Liming
Abstract: This article investigates the N -be-that construction in popular and professional science articles with a focus on shell nouns. This examination of shell-noun use in two corpora, one consisting of popular science articles and the other of research articles, reveals the preferred ways of evaluation in these two genres. The study shows that, despite the overall similarity in semantic distribution, there are distinct variations in shell-noun use between the two genres. Popular science writers are more inclined to use this focus construction and tend to be more explicit in making evaluations than are professional science writers. In popular science articles, shell nouns express more epistemic certainty, news-worthiness, and subjectivity, whereas in research articles these nouns express more tentativeness, objectivity, and scientific rationality. This comparative study further expands current understanding of the evaluative functions of shell-noun use and can also help cultivate writers' genre awareness. Highlights: The overall semantic distribution is similar, with factual nouns in the majority. Variations in shell-noun use reflect writers' preferred ways of evaluation across genres. More certainty, news-worthiness, and subjectivity are found in popular science articles. More tentativeness, objectivity, and rationality are found in research articles. The study extends current understanding of the evaluative functions of shell nouns and helps raise genre awareness.